Apakah Kepercayaan dan Ketergantungan Berpengaruh Terhadap Repurchase Intention Hand and Body Lotion Citra? - Mahardhika, Mustafidah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The aim of this research is to determine the influence of trust on repurchase intention of Citra hand body lotion and the influence of dependence on repurchase intention of Citra hand body lotion. Primarily, this is a quantitative research design. To determine whether or not there is an influence of trust and dependence, research data analysis was carried out using multiple linear regression analysis. The result is that trust and dependence influence Citra hand body lotion repurchase intention, both partially and simultaneously. These results contribute to the novelty that several consumers of Citra hand body lotion actually have a sense of trust and dependence on this skin care product.